Are Sectoral Outputs in Pakistan Led by Energy Consumption - Venus, Khim-Sen Liew; Wong, Wing-Keung; Thurai Murugan, Nathan (AccessEcon, 2012)
We investigate the relationships between energy consumption and the outputs of the main economics sectors in Pakistan, where energy shortage is a major challenge faced by the economy. It is found that services and industrial output, which make up of fourth-fifth of Pakistan gross domestic product, are not led by energy consumption in the country. Hence, the government of Pakistan could impose energy conservation measures on these two sectors with little or no adverse effect on the growth of those sectors.